Transition of Accessory and Non-Accessory Securities with Cession by Operation of Law (Cessio Legis) - Renato Vrenčur; Denis Baghrizabehi; Kristjan Zahrastnik (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci)
Financial and commercial claims are usually secured by personal and real securities in commercial practice. Different types of securities are used, both accessory and non-accessory. The question arises as to how to interpret the provisions on subrogation or cession by operation of law (cessio legis) in relation to the transfer of non-accessory securities to the performer of the obligation, particularly in the case of sureties. A surety undertakes to perform a debtor’s obligation (not its own obligation) to the debtor’s creditor. Consequently, after the performance, the creditor’s claim toward the debtor passes onto the surety with all the accessory rights and guarantees. The key question to be answered in this article is whether non-accessory rights pass to the surety as well (who has fulfilled the obligation of the principal debtor), or whether the creditor must make a corresponding (additional) transaction to pass these rights. The article presents key findings in this regard, along with an analysis of the position of the surety in insolvency proceedings.